Awareness, Barriers and Concerns of Adolescents Toward the COVID-19 Vaccine: A Cross-Sectional Study in Singapore - Oka, Prawira; Thia, Benecia Wan Qing; Gunalan, Shyna Zhuoying; Kwan, Janae Rae Yann; Ng, Ding Xuan; Aau, Wai Keong; Wee, Juan Dee; Tan, Ngiap Chuan (Frontiers in Public Health, 2022)
Background COVID-19 vaccination is a key public health measure to mitigate the crippling effects of the pandemic. COVID-19 vaccination began in adults and targeted adolescents at a later stage. However, medical decision-making on its uptake among the latter was unknown, which could be affected by their literacy and concerns about the vaccine. The study aimed to elucidate the awareness, concerns and barriers of adolescents toward the COVID-19 vaccine. Methods A cross-sectional online survey using a self-developed questionnaire was conducted between June to November 2021. The adolescent participants were students from institutes of post-secondary education who were recruited via convenience sampling. The data were collated from an officially approved electronic platform, audited and analyzed. Continuous and categorical variables were expressed as mean (standard deviation) and percentages, respectively. Results A total of 460 adolescents participated in the study (mean age: 16.99 ± 0.99; 73% female). Most of them (91.5%) were aware of the COVID-19 vaccines. The main barriers to vaccination were uncertainty about long-term health risks (38.6%) and vaccine efficacy (37.3%). Regarding the potential vaccine side effects, they were concerned about: anaphylactic shock (73.2%), low blood pressure (58.3%) and fast heartbeat (58.0%). Only 58% expressed willingness for repeated COVID-19 vaccination. Conclusion Despite high COVID-19 vaccine awareness, the adolescents were concerned about the potentially severe but rare side-effects. The study identified apprehension regarding vaccine efficacy and the potential long-term health impact as the main barriers to vaccination. Future studies should address these concerns to scale vaccination programs among adolescents.